2011
DOI: 10.3855/jidc.1625
|View full text |Cite
|
Sign up to set email alerts
|

Development of modified diagnostic criteria for bacterial vaginosis at peripheral health centres in developing countries

Abstract: Introduction: Bacterial vaginosis (BV) is the commonest cause of abnormal vaginal discharge in women of child-bearing age and is associated with increased susceptibility to HIV-AIDS and sexually transmitted diseases. In obstetrics, BV has been implicated in causing various complications. In clinical practice, BV is diagnosed using Amsel criteria and Nugent scoring. Using modified Amsel criteria, we determined that the fulfilling of any two instead of three criteria can be diagnostic of BV. Methodology: This pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
2
11
2
Order By: Relevance
“…This result is similar with the finding by Mastrobattista and his colleagues [14]. Many studies suggested that raised vaginal pH is recognized as the least specific criteria [14,19] and it is confirmed in our investigation. The lower specificity and positive predictive value of vaginal pH compared to others clinical criteria in this study indicates the presence of other genital tract infection or factor which increases pH without the presence of disturbed vaginal flora.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This result is similar with the finding by Mastrobattista and his colleagues [14]. Many studies suggested that raised vaginal pH is recognized as the least specific criteria [14,19] and it is confirmed in our investigation. The lower specificity and positive predictive value of vaginal pH compared to others clinical criteria in this study indicates the presence of other genital tract infection or factor which increases pH without the presence of disturbed vaginal flora.…”
Section: Discussionsupporting
confidence: 82%
“…It had a higher sensitivity, specificity and positive and negative predictive value. This is consistent with the study done by other researcher's [16][17][18][19]. But this is not consistent with Dadhwal et al, [11].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In particular, the causal relationship between BV and PTB among women from various ethnic groups has been consistently noted. A few studies have reported the magnitude of BV during pregnancy among Indian women (6.4% [ 17 ], 24.3% [ 18 ], and 12% [ 19 ]); however, the paucity of data regarding the potential association of BV with PTB among these women is evident in the published literature. A lower rate of BV (6%) could possibly be attributed to the socioeconomic and lifestyle factors of our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrate that BV diagnosis using only two Amsel criteria (vs. four) has similar sensitivity and specificity compared to Nugent scoring. 2829 Other studies indicate that the sensitivity of Amsel criteria can be low compared with Nugent scoring. 3031 In this study, the variability in the two diagnostic methods was clearly demonstrated: all women had symptomatic BV at enrollment by modified Amsel criteria, but only 80% had BV according to Nugent scoring.…”
Section: Commentmentioning
confidence: 99%